Where Is Leisure When Death Is Present?. (3rd March 2021) - Fox, Karen M.; McDermott, Lisa
Abstract: For many, the COVID-19 pandemic is the overwhelming, ever-present reality of dying—of loved ones, close family members, dear friends, colleagues, or patients. Fear, avoidance of or lack of time for essential conversations, physical separation during final moments, and lack of rituals for these contingencies leave individuals alone with loss, mourning, and grieving. How is leisure relevant during such realities? Historically, leisure has been present across diverse cultural dying and death practices: art, music, dance, theater, play, contemplation, rituals, and somatic practices. These connect individuals with life forces even as some are absent in the flesh. In truth, we are all experiencing dying-death-mourning-beginning again during the COVID-19 pandemic. Josef Pieper's (2017, 2016, 2011, 1999, 1988) philosophy hints of leisure as context for the meaning, purpose, and comfort in such trying times: contemplating one's place in a changing world/universe and celebrating or affirming that relationship in community.